2013
DOI: 10.4103/0971-3026.120273
|View full text |Cite
|
Sign up to set email alerts
|

Variations of celiac axis, common hepatic artery and its branches in 600 patients

Abstract: Purpose:To evaluate the spectrum of celiac axis, common hepatic artery (CHA), right, left, middle hepatic artery and gastroduodenal artery variations by using spiral computed tomography (CT).Materials and Methods:A retrospective review of Multidetector CT (MDCT) abdominal angiography scans was performed in patients sent for various liver and other abdominal pathologies between January 2012 and February 2013. A total of 600 patients were evaluated. Definitions of CHA, ambiguous celiac axis, course and division … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
57
4
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 13 publications
(23 reference statements)
13
57
4
10
Order By: Relevance
“…The prevalence of anatomical variations of the CeT found in this study was three times higher than that reported in other studies ranging from 10-12% [4,5,14,24,25]. This difference should be revalidated in other studies with a bigger Latin American population, but at this time we didn't found any study using latin american patients.…”
Section: Discussioncontrasting
confidence: 54%
“…The prevalence of anatomical variations of the CeT found in this study was three times higher than that reported in other studies ranging from 10-12% [4,5,14,24,25]. This difference should be revalidated in other studies with a bigger Latin American population, but at this time we didn't found any study using latin american patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Regarding aberrant left hepatic artery they observed 90 cases (18 %) of ReLHA and 175 cases (35 %) of AcLHA -a total of 265 cases (53 %) aberrant left hepatic artery. Sureka et al [11] found ReRHA (15.16 %) , AcRHA (5.16%) , ReLHA (10.8%) , AcLHA (7.6%) in their study. In Adachi study [12] AcLHA arose from LGA in 17.9% and AcRHA from SMA in 10.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of the circles, by anatomical variation or by dissection may produce inadvertent ischemia of the gastric tube leading to complications. CT angiography, performed nowadays more frequently should be carefully studied before surgery to anticipate those anatomical variations (19). Interesting is to know the gastrocolic vein of Henle and the variable course of the left gastroepiploic vein that runs in 30% of the patients in front of the common hepatic artery and in 70% behind it.…”
Section: Discussionmentioning
confidence: 99%